Valuing the law of public procurements and its role in sustainable development - SOLTANE, Amar (Journal of Human Sciences, 2025)
Recently issued legislation on public procurements (Law No. 23 12 of 5 August 2023) to crown a series of successive texts that reflected the developments of public spending and the legislator's view of the way it is regulated. Through this study, we try to clarify the reality of public procurements in Algeria and their relationship to sustainable development, and to review some aspects of valuation and rationalization of public procurements, especially what was brought by the recent legislation again in this field, and to come up with some constructive proposals.